Sequential therapy in treatment of patients with metastatic renal cell carcinoma - Żołnierek, Jakub (Contemporary Oncology/Współczesna Onkologia, 2009)
As metastatic renal cell carcinoma (mRCC) is particularly resistant to available treatment modalities there is a strong need for development of new strategies to be used in therapy of patients with such diagnosis. Immunotherapy – in Poland typically based on subcutaneous injections of interferon a – although having the ability to eradicate tumour does so only in a small percentage of patients. Because of its relatively low efficacy the indications for use of immunotherapy are restricted. Thanks to the introduction of novel drugs into clinical practice – tyrosine and serine-threonine kinase inhibitors and monoclonal antibodies – objective responses are seen more often. Despite their significant influence on progression-free survival, the impact on overall survival is not so clear and complete remissions are casuistic. Pharmacotherapy of metastatic renal cell cancer is still the palliative treatment, aimed at decelerating tumour growth and delaying the moment it reaches its critical burden. For this reason it is crucial to look for new strategies of care. One of them is sequential therapy – an attractive option available now and with predictive and tolerant toxicity. The paper provides a short discussion of the problem.